Simple but Complex—A Laying Hen Study as Proof of Concept of a Novel Method for Cognitive Enrichment and Research - Schmelz, Martin; Krause, E. Tobias (Frontiers in Animal Science, 2021)
Enrichment can reduce stress and stereotypic behavior and therefore enhance captive animal welfare. In cognitive enrichment, cognitive tasks engage and challenge the animals' natural behavioral repertoire and provide mental stimulation. Enrichment with similarities to "puzzle boxes" in cognitive research is widespread in zoos but rarely applied in commercial farming, as it requires costly time and effort. Here, we introduce a flexible method for cognitive enrichment and research. The test battery apparatus (TBA) is a configurable cubic box with frames for interchangeable test panels, each holding a problem-solving task that must be solved for a food reward. As a proof of concept, we report observations and first results from two groups of laying hens (Gallus gallus forma domestica; 52 birds in total) to show the TBA's feasibility in commercial farming and to investigate the animals' spontaneous interaction with four test panels. While we could not reliably identify individuals, we found the majority of the hens highly motivated to engage with the device. At least five individuals in each group were successful and there was a significant gradient of success rates across the four panels. As the implementation and maintenance required little time and effort, the TBA is promising as a cognitive enrichment device in farm settings. Its potentially limitless configurations allow diverse opportunities for cognitive and behavioral engagement in the long term. While further studies will be crucial to validate welfare effects and problem-solving tasks, the TBA is simple in its application but complex in its possibilities.